1971
DOI: 10.1111/j.1365-2672.1971.tb02304.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Coulter Counter to Count Cells of Streptococcus faecalis

Abstract: Summary. The suitability of the Coulter electronic particle counter for counting chains of cells of Streptococcus faecalis was investigated. Growth curves produced from electronic counts had similar characteristics to curves produced from nephelometer readings, viable pour plate counts and total counts performed with a Thoma counting chamber. The validity of comparing counts obtained using different counting parameters is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1975
1975
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Least disparity occurred at the end of exponential growth (6 h) when the culture contained 97.5 % viable cells. Andrew & Westwood (1971) found that a strain of Streptococcus faecalis had viable counts greater than Coulter counts. They postulated that cell chains, recorded as single units by the Coulter Counter, split into smaller units during serial dilution to elevate the viable count.…”
Section: Growth Curvementioning
confidence: 98%
See 1 more Smart Citation
“…Least disparity occurred at the end of exponential growth (6 h) when the culture contained 97.5 % viable cells. Andrew & Westwood (1971) found that a strain of Streptococcus faecalis had viable counts greater than Coulter counts. They postulated that cell chains, recorded as single units by the Coulter Counter, split into smaller units during serial dilution to elevate the viable count.…”
Section: Growth Curvementioning
confidence: 98%
“…Most of the earlier work with Coulter Counters was performed with pure cultures where experimental conditions were controlled to provide optimum working conditions. In these circumstances the instrument generally provided total counts and/or size distribution curves of cells in various microbiological systems ; sometimes purely as an alternative to established methods of performing these functions (Mountney & O'Malley, 1966;Adams, 1966;Glynn & Medhurst, 1967), but mainly in an analytical capacity for studying aspects of cell and spore physiology to indicate specific metabolic activities (Lark & Lark, 1960;Toennies, Iszard, Rogers & Shockman, 1961 ; Knisely & Throop, 1965; Garrett & Miller, 1965; Gorchein, Neuberger & Tait, 1967;Andrew & Westwood, 1971). Spore volume and shape of volume distribution curves have also been assessed for possible use in fungal taxonomy (Barnes & Parker, 1968).…”
mentioning
confidence: 99%
“…Several studies have demonstrated its utility for counting various bacterial organisms from Bacillus species to cocci. 5,6 In one later study, a direct linear relationship was demonstrated when counts of Escherichia coli, Staphylococcus aureus, and Streptococcus faecalis obtained by the Coulter counter were compared with those obtained by the pour plate technique. The ease and rapidity of counting with the Coulter was felt to make this technique superior to the pour plate method.…”
Section: Discussionmentioning
confidence: 95%
“…The currently available counting methods can be divided into two broad categories: those for counting high concentrations and those for counting low concentrations of particles. For counting high concentrations of particles on the order of 10 6 particles/ml, the electrical sensing zone (Coulter counter) technique 4,5) or flow cytometry 6,7) are used. These techniques count particles by monitoring the change in impedance or light scattering, respectively, and can be used to determine particle concentrations within about 10% accuracy on the order of 10 6 particles/ml.…”
Section: Introductionmentioning
confidence: 99%